Penyuluhan Tentang Alur Pendaftaran Pasien Rawat Jalan Di Rumah Sakit - Langingi, Ake; Pongantung, Henny; Suparlan, Monica Sri Rejeki; Watak, Chintami Luciana Watak; Kasenda, Adelia; Roringpandey, Eklesia Roringpandey (Journal of Excellence Humanities and Religiosity, 2025)
Patient registration is the initial stage of medical records in every health care facility, at the patient registration site the patient's personal identity data will be recorded as well as the purpose of his visit to the hospital. The reason for choosing the service topic is because many patients and families still do not understand the flow of outpatient patient registration at the hospital. The service method used is the pre-post test method through giving questionnaires about knowledge about the flow of outpatient registration. The result of this service activity is an increase in knowledge about the flow of outpatient patient registration. This activity is very important because patients and families need fast and precise service, so it is necessary to provide counseling or socialization about the flow of outpatient registration.